A rare case of intramedullary solitary juvenile xanthogranuloma of the lumbar spine in the adult: a case report - Pirillo, Vania; Prontera, Andrea; Rizzo, Paolo; Cecchi, Paolo Cipriano; Maffei, Martin; Schwarz, Andreas (Journal of Spine Surgery, 2017)
Solitary juvenile xanthogranuloma (SJX) of the spine is an extremely rare proliferative histiocytic disorder with only few cases reported in literature. We present the first case of intramedullary spinal SJX. A 22-year-old male presented with a nine-month history of progressively worsening sphincteric disturbances and saddle hypoesthesia. Magnetic resonance imaging showed an intra-axial lesion located in the conus medullaris; T1 hypointense, T2 iso-hyperintense and uniformly enhancing after contrast administration. The lesion was removed through a T12–L1 laminectomy and a median myelotomy with neurophysiological monitoring. Histological examination and immunohistochemical testing confirmed the diagnosis of SJX. Due to the intramedullary localization and the absence of a clear cleavage plane, radical removal was not possible. The tumor subsequently recurred and new surgical procedures were necessary followed by adjuvant radiotherapy. Patient made good neurological recovery. Three years after the latest treatment, MRI showed no recurrence. In accordance with the literature, the treatment of choice for SJX its radical removal, or subtotal removal followed by adjuvant radiotherapy.